Acetylation of intact white rice grains to alter the physicochemical properties. (March 2020) - Nawaz, Malik Adil; Singh, Tanoj Kumar; Tan, Melvin; Prakash, Sangeeta; Fukai, Shu; Bhandari, Bhesh
Abstract: The effect of acetylation of milled rice grains of selected varieties (TDK 8, YRW 4, Reiziq, Amber 33, and SHZ 2) with varying apparent amylose contents (3.8–26.6%) on their physicochemical properties was investigated. Milled rice samples were treated with different acetic anhydride concentrations (0.004–0.04 g per 100 g of milled rice samples in 225 mL of water). Results showed that glutinous (TDK 8), very low amylose (YRW 4) and low amylose containing varieties (Reiziq) were prone to acetylation even with 0.004 g of acetic anhydride. X-ray diffraction patterns showed an increase in the crystallinity in acetylated samples and formation of V-type crystals, suggesting the possible interaction of acetic anhydride with starch. Acetylation of rice grains resulted in reduced peak and final viscosities and gel strength, particularly in glutinous (TDK 8) and very low amylose (YRW 4) rice. Differential calorimetric study showed that acetic anhydride treatment resulted in reduced thermal transition temperatures and enthalpy of all varieties. Although increase in the retrogradation thermal temperatures was observed, the enthalpy of retrogradation was reduced with increasing acetylation, suggesting that the extent of starch retrogradation was lower in all varieties with more prominent reduction in the glutinous type. Furthermore, the texture of cooked acetic anhydride treated rice grains was less hard and showed more adhesiveness. This study demonstrated that the acetylation of rice grains (instead of flour) was successfully achieved, showing the potential of applying acetylation to alter the textural, pasting, thermal and retrogradation properties of rice. Graphical abstract: Image 1 Highlights: Intact starch in whole grain was easily acetylated even with dilute acetic anhydride. Acetylation resulted in increased crystallinity and formation of V-type crystals. Acetic anhydride treatment reduced swelling and final viscosity. Acetic anhydride treatment reduced gelatinization and retrogradation enthalpy. Significant ( p  < 0.05) increase in adhesiveness was found in acetylated rice grains.